THU0080 Lipid Testing and Management among Rheumatoid Arthritis Patients Compared To Patients with Diabetes and The General Population. (15th July 2016) - Navarro-Millan, I.; Yang, S.; Chen, L.; Safford, M.M.; Yun, H.; Zhang, J.; Muntner, P.; Saag, K.; Curtis, J.R.
Abstract : Background: Patients with rheumatoid arthritis (RA) have high coronary heart disease (CHD) burden. Limited data suggest that these patients may be screened less frequently than other patients with similar CHD risk. Objectives: To evaluate the rate of lipid testing and management among RA patients and compare it both to the general population and diabetes (DM) patients. Methods: We used a mix of private and public health plans claims data from 2006 to 2010 with medical and pharmacy coverage. Eligible participants were required to 1) have at least 12 months of continuous medical and pharmacy coverage (baseline period), and 2) have 2+ physician diagnosis and relevant medications to categorize them as having 1) RA and DM; 2) RA only; 3) DM only; 4) Neither RA nor DM. Patients with prevalent myocardial infarction (MI)/stroke/CHD during baseline were excluded. We calculated the proportion of patients with low density lipoprotein (LDL) lab test. In a subgroup analysis, we determined the proportion of patients with lab results available with LDL ≥130 mg/dL that initiated treatment with statins. We use chi-square tests to compare differences between the 4 cohorts in the proportion tested for LDL and initiating statins. Results: There were 428, 109 eligible patients distributed between the 4 cohorts (Table). Overall, 60% were women. The overall age distribution was: 12% ≤40; 29%, 41–65; and 59% >65 years old. RA patients were less frequently tested for LDL compared to DM patients, with or without RA (p-value <0.001 for all comparisons). Conditional on having LDL ≥130 mg/dL, RA patients were less likely to be started on a statin compared to DM patients (p-value <0.001), and were marginally more likely to be initiated on statins compared to the general population (p-value =0.045). There was no difference in the statin prescription trend after an LDL ≥130 mg/dL between DM and RA patients compared to only RA patients (p-value =0.083) Conclusions: RA patients are less frequently screened and managed for hyperlipidemia compared DM patients. Despite higher CHD risks in RA patients, hyperlipidemia screening and treatment rates in RA patients were no better than the general population. Further studies to investigate the reasons and potential interventions to ameliorate this care gap among RA patients are needed. Disclosure of Interest: None declared